(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Because of human and technical improvements, the demand for freshwater has increased by leaps and bounds globally in agricultural, industrial, and home sectors, resulting in over-exploitation of freshwater resources. The management of wastewater generated as a by-product of these industries’ different human activities is a global challenge today. Greywater (GW) is a type of wastewater produced in the domestic sector. Wetlands are locations whereby water covers the soil or is present at or near the soil’s surface all year or for variable periods of time throughout the year, including the growing season. Water saturation (hydrology) influences how soil develops as well as the sorts of biological communities that live in and on the soil. Wetlands may provide habitat for both marine and terrestrial organisms. The presence of water over an extended period of time provides conditions that encourage the growth of particularly adapted plants (hydrophytes) and the creation of distinctive wetland (hydric) soils. The water from the shower, sinks, and bathrooms is commonly referred to as "grey water." With proper treatment, greywater can be used for irrigation, allowing residential and backyard gardens to reconnect to the natural water cycle. "Root zone" is a technique that has proven to be particularly effective in recycling greywater. In this project artificial wetland has been constructed with various layers of materials using root zone technique using following plants Colocassia and canaindica. The greywater was passed through the assembly which had been constructed which consisted of settling tank, wetland unit, filtration unit. The samples of grey water were taken. COD, BOD, TDS, TSS were performed to find out these properties. Then grey water was passed through the assembly and these tests were conducted. The values show us there is decrease in COD, BOD, TSS and TDS. This decrease shows that the grey water can be for gardening purpose in homes.